Collision repair fundamentals - Magee, Robert (Thomson/Delmar learning, 2008)
This all new textbook was written and illustrated to introduce readers to automotive collision repair. Collision Repair Fundamentals stresses the repair of minor body damage and repainting, as well as advanced repairs such as frame straightening and structural panel replacement. Coverage has been added on the latest high-efficiency spray guns, UV-primers, primer-surfacers with a built in guide-coat action, aluminum weld-rivet construction, and much more. Each service-oriented chapter is accompanied by a practice ASE test featuring numerous ASE-style questions